Academic Self-Efficacy with Academic Stres in Final Year Students - Christy, Litani Elsa Adiela; Soetjiningsih, Christiana Hari (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
This quantitative-correlational study aims to determine the relationship between Academic self-efficacy and Academic stres in final year students from NTT. In this study, researchers used purposive sampling techniques with a total of 102 final year students who were working on their thesis and came from NTT. The research instrument used an Academic self-efficacy scale and an Academic stres scale. This study used two scales, namely Academic self-efficacy, and Academic stres. The results showed a correlation of r = -0.468 and a significance value of 0.000 (p < 0.05) which means there is a relationship between Academic self-efficacy and Academic stres in final year students who are working on their thesis and come from NTT. The higher the Academic self-efficacy, the lower the Academic stres. Conversely, the lower the Academic self-efficacy, the higher the Academic stres. The results of this study can be a reference for final year students who are working on their thesis and come from NTT to increase their Academic self-efficacy to minimize Academic stres in final year students from NTT who are working on their thesis.Penelitian kuantitatif - korelasional ini bertujuan untuk mengetahui hubungan antara Academic self-efficacy dengan stres akademik pada mahasiswa tingkat akhir asal NTT. Pada penelitian ini, peneliti menggunakan teknik purposive sampling dengan total partisipan sebanyak 102 mahasiswa tingkat akhir yang sedang mengerjakan skripsi dan berasal dari NTT. Instrumen penelitian menggunakan skala Academic self-efficacy dan skala stres akademik. Penelitian ini menggunakan dua skala yaitu Academic self-efficacy dan stres akademik. Hasil penelitian menunjukkan adanya korelasi sebesar r = -0,468 dan nilai signifikansi sebesar 0,000 (p<0,05) yang berarti ada hubungan Academic self-efficacy dengan stres akademik pada mahasiswa tingkat akhir yang sedang mengerjakan skripsi dan berasal dari NTT. Makin tinggi Academic self-efficacy maka semakin rendah stres akademik. Sebaliknya semakin rendah Academic self-efficacy maka semakin tinggi stres akademik. Hasil dari penelitian ini bisa menjadi acuan untuk para mahasiswa tingkat akhir yang sedang mengerjakan skripsi dan berasal dari NTT agar dapat meningkatkan Academic self-efficacynya sehingga dapat meminimalisir stres akademik pada mahasiswa tingkat akhir asal NTT yang sedang mengerjakan skripsi.